Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2017)
Two new species of Nullana DeLong, 1980 are described and illustrated: N. albinoi sp. nov. and N. sakakibarai sp. nov., both from the state of Paraná, Brazil. Two new synonyms and a new combination are proposed. A key to the 10 known species of Nullana are presented and Nullana gelbana is newly recorded from Paraná State, Brazil.